Investigation of conventional and rheological properties of bitumen modified with Selenizza natural asphalt - Kok, Baha Vural; Yalcin, Erkut; Yilmaz, Mehmet; Buyuk, Baris (Gazi Univ, Fac Engineering Architecture, 2023)
Polymer type additives are generally used to improve the properties of bituminous mixtures. However, the limited production quantities and high costs of these additives bring the use of lower-cost and natural materials as additives. In this study, the effects of Selenizza bitumen, a natural asphalt type, on the softening point, penetration, viscosity, rutting parameter, creep recovery and low temperature properties of bituminous binders were investigated. The low and high temperature performance of Selenizza bitumen-containing binders with different content was compared with pure and 3% Styrene-butadiene-styrene modified binders. As a result, it has been determined that Selenizza modification will show a significant performance increase compared to pure binder especially in regions with high temperature and high traffic volume. It has been determined that the addition of 15% Selenizza increases the high temperature performance level of the pure binder by one degree and is sufficient to provide similar high temperature performance with the 3% SBS modification, but should be used at a maximum of 7% in terms of low temperature.
Keywords: Natural asphalt; Modification; SBS; Conventional properties; Rheological properties